Geoeconomics of the sustainable development goals - Morales, Lucía (Lecturer in economics and finance); Andréosso-O'Callaghan, Bernadette, 1959-; Rajmil, Daniel (Routledge, 2025)
"In 2015, the United Nations introduced its very ambitious 2030 Agenda, known as the Sustainable Developmental Goals or SDGs. The SDGs provide a comprehensive list of goals and targets to address social, economic and environmental issues. Different areas of expertise are brought together, examining the main challenges associated with the effects of "climate change" and the broader scope of the SDGs through the lenses of the geo-economics and geopolitics of sustainability. The book sheds light on the growing connections between the economic and financial fields and their impact on defining the international order and its economy. It examines the importance of trade and economic integration in promoting sustainable development and achieving the SDGs. The role of supranational organisations like the United Nations, the World Trade Organisation and the IMF in supporting the SDGs within the context of the world's most advanced economies and those less developed; the influence of economic diplomacy and geopolitical rivalries on progress towards the SDGs; the changing global balance of power and the significance of technology and innovation; as well as the role of emerging and less developed economies in enabling sustainable development. The book offers insights into practical issues linked to theory and applied frameworks, underscoring the significant challenges associated with sustainable development, the global economic and political reality, and how political tensions affect the global economy. The book supports students through the established disciplines of economics, finance, political science, and law and provides academics with new research and theory-building tools"-- Provided by publisher.
Keywords: Sustainable development.; Social policy.; Environmental policy.; World politics.; elektronické knihy; electronic books